A Study on Impact of Bank Interest Rates on Consumer Spending Behaviour - P Hameem Khan, Bakkiasri. P, Soundarya Anand, Ramya.V, (European Economic Letters (EEL), 2024)
The research examines how bank interest rates affect spending. It also examines the complex relationships between monetary policy, money management, and business. The research employs statistical models and secondary data analysis to examine how interest rate changes impact borrowing, debt, the industry, how various groups behave, and how people's thinking affect their behavior. Low interest rates encourage borrowing and spending, particularly on houses and autos. High rates make consumers cautious and less willing to borrow. Interest rate increases impact various populations differently. Rate adjustments effect younger and lower-income consumers disproportionately. Knowing how individuals think about risk, income, and interest rates might help them make better financial decisions. The research emphasizes the need of clear monetary regulations, repayable loans, and money education programs to create financial strength and prudent spending. This allows governments, financial institutions, corporations, and consumers to create personalized regulations, flexible lending practices, sector-specific initiatives, and consumer education programs. These proposals aim to aid clients with unpredictable finances, manage shifting interest rates, and enhance long-term economic development. This research helps us understand how interest rates impact people's purchasing behaviors and find strategies to make them healthier, wealthier, and more economically robust.